Factors associated with physician burnout syndrome: a comparative analysis - Stojanović, Marko; Rančić, Nataša; Stojanović, Miodrag (Vojnosanitetski pregled, 2025)
Background/Aim. Burnout syndrome (BS) can occur in doctors at different levels of health care. The aim of this study was to identify the prevalence of BS and compare the differences among physicians in health institutions in Southeast Serbia (SES). Methods. A multicenter, questionnaire-based cross-sectional study was conducted among 373 physicians (252 female and 121 male) from primary, secondary, and tertiary care institutions in SES from 2023 to 2024. The Maslach Burnout Inventory-Human Services Survey (MBI-HSS) was applied. Results. A significantly higher score on the emotional exhaustion (EE) subscale was observed in physicians older than 55 years (p
Keywords: burnout, psychological; physicians; primary health care; serbia; specialization; surveys and questionnaires; tertiary care centers